The Effect of Intrinsic Motivation, Workload, and Work Environment on Employee Job Satisfaction (at the Office of the Port Master and Port Authority Class II Cirebon) - Laenah Dwi Cahyani; Putri Rafi Anisa; Budi Agung Prasetya (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study analyzes the influence of intrinsic motivation, workload, and work environment on employee job satisfaction at the Harbor Master Authority and Port Office (KSOP). With a quantitative approach, data were collected through questionnaires from 100 employees and analyzed using multiple linear regression in SPSS. The results showed that intrinsic motivation and work environment have a positive and significant effect on job satisfaction, with significance values of 0.012 and 0.000, respectively. In contrast, workload had no significant effect (p > 0.05). The regression model explained 58.9% of the variation in job satisfaction. In conclusion, increasing intrinsic motivation and creating a conducive work environment play an important role in increasing employee job satisfaction. Further studies are recommended to explore other factors and conduct longitudinal research.